Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (Jones and Bartlett, 2006)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Antibiotic-taking experiences of undergraduate college students. - Aronson, Barbara S (Journal of the American Academy of Nurse Practitioners, 2006)
Purpose: The purpose of this qualitative descriptive study was to explore the medication-taking experiences of undergraduate college students prescribed short-term antibiotic therapies and to describe factors influencing their adherence. Data sources: Thirty-four undergraduate students prescribed antibiotics for treatment of an acute infectious illness at a large university health center were recruited to participate in this study. Semistructured telephone interviews were conducted after students finished their course of treatment. Qualitative descriptive content analysis was used to analyze the transcripts typed from the audio-taped phone interviews. Conclusions: The main theme that emerged from the data was antibiotic-taking self-management. Most participants were able to adapt medication regimens into their daily routines, and used events in their day and specific reminder strategies to help them to remember to take their medications. This occurred despite an ever-changing class and work schedule and being prescribed complex, lengthy antibiotic regimens. Most dosing errors occurred during times when schedules changed or students were off campus during weekends or college breaks. A small number of students discontinued therapy early because of side effects or forgetfulness. Implications for practice: By understanding factors that influence antibiotic adherence from a college student perspective, healthcare providers can suggest strategies to promote adherence that are tailored to the specific needs of this unique population. © 2006 American Academy of Nurse Practitioners.
6 citations (Crossref) [2023-10-31] Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, Connecticut 06515, USA. aronsonb1@southernct.edu
Keywords: *Anti-Bacterial Agents/tu [Therapeutic Use]; *Patient Compliance; *Self Care; *Students; Adolescent; Adult; Anti-Bacterial Agents; Antibiotic adherence; College students; Female; Humans; Male; Medication self-management; Patient Compliance; Self Care; Students; United States; adolescent; adult; antiinfective agent; article; dept.nur; female; human; male; patient compliance; self care; student